2013
DOI: 10.1007/s00277-013-1924-9
|View full text |Cite
|
Sign up to set email alerts
|

BAFF and APRIL as TNF superfamily molecules and angiogenesis parallel progression of human multiple myeloma

Abstract: Tumour necrosis factor alpha (TNF-α) is an inflammatory cytokine with a wide spectrum of biological activity, including angiogenesis. B cell activating factor (BAFF) and a proliferation-inducing ligand (APRIL) are members of the TNF-α family. Vascular endothelial growth factor (VEGF), on the other hand, is one of the most characteristic pro-angiogenic cytokines produced by multiple cell types in multiple myeloma (MM). We have analysed BAFF and APRIL concentrations in parallel with pro-angiogenic cytokines in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 44 publications
8
36
0
1
Order By: Relevance
“…The highest absorbance occurred at concentrations of 100 ng/mL BCMA and 1 ng/mL BAFF (Fig. 1A), which are similar to those found in plasma from multiple myeloma patients (28,29).…”
Section: Resultssupporting
confidence: 65%
“…The highest absorbance occurred at concentrations of 100 ng/mL BCMA and 1 ng/mL BAFF (Fig. 1A), which are similar to those found in plasma from multiple myeloma patients (28,29).…”
Section: Resultssupporting
confidence: 65%
“…Our data suggested that BAFF was produced by the stromal compartment, specifically the osteoclast compartment, and that treatment with an anti-BAFF antibody resulted in antitumor activity and decreased osteoclast numbers (4). Others have shown that elevated BAFF and APRIL levels are associated with poorer outcome and more aggressive disease (9,10). This association of elevated BAFF levels with poorer outcomes, along with the role of BAFF in the survival of multiple myeloma cells, provided the rationale for targeting BAFF in relapsed/refractory multiple myeloma.…”
Section: Introductionmentioning
confidence: 85%
“…These results further support a recent study showing that APRIL, but not BAFF, is correlated with expression of VEGF and its receptors, MVD and CD138, and with progression of human MM. 19 Furthermore, in a xenogeneic model where MM cells were subcutaneously injected into SCID mice deficient in APRIL, APRIL by itself was shown to be essential for in vivo MM development. 25 Moreover, the lack of APRIL equally impaired U266 (TACI Because BCMA overexpression by itself is sufficient to augment MM cell proliferation and survival, the majority of MM cell lines (also TACI low/neg ) may bypass APRIL-induced proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] It is elevated in the circulation of MM patients vs normal donors. 18,19 Besides binding to BCMA, APRIL also binds to the receptor transmembrane activator and calcium modulator (TACI), which is also overexpressed on malignant PCs from patients vs normal donors. 20 Despite its association with survival of MM cells on the BM microenvironment, 20,21 TACI expression on MM cell lines and patient MM cells is reported to be variable and lower compared with BCMA.…”
Section: Introductionmentioning
confidence: 99%